2015
DOI: 10.1007/s11605-015-2787-2
|View full text |Cite
|
Sign up to set email alerts
|

No Gut Syndrome: Near Total Enterectomy

Abstract: In adult patients, removal of the entire jejunum and ileum (a near total enterectomy (NTE)) is considered a non-survivable event as patients undergoing this procedure might also suffer from an underlying illness that will lead to bowel necrosis such as septic or cardiac shock and respiratory failure. Parenteral nutrition (PN) dependency with its associated complications and quality of life issues further complicates management decisions in this group of patients. In the following report, we discuss our institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…However, it has been observed that with the passage of time these episodes gradually reduce in frequency as well as severity [15] , [16] . Our previous experiences along with our experience in this case as well, have been encouraging in this regard [2] . Other options are also available, but have not been as successful.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…However, it has been observed that with the passage of time these episodes gradually reduce in frequency as well as severity [15] , [16] . Our previous experiences along with our experience in this case as well, have been encouraging in this regard [2] . Other options are also available, but have not been as successful.…”
Section: Discussionsupporting
confidence: 65%
“…We therefore feel, this entity needs to continue being reported so that previous results and subsequent decisions can be discussed with the patient and patient’s family should this scenario occur in clinical practice. We have previously reported two cases and a review of literature on patients who have undergone a NTE and have been successfully maintained on PN [2] . Since then we have managed an additional case that has been reported here in a similar manner and found an additional citation in the literature [4] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although formation of a duodenocolic anastomosis is unusual, some reports support its effectiveness in restoring intestinal continuity. A recent review analyzed 28 patients who underwent total small bowel resection in the last 70 years [ 4 ]. Establishment of bowel continuity by means of a duodenocolic anastomosis was shown to be a viable option in hemodynamically stable patients.…”
Section: Discussionmentioning
confidence: 99%
“…1 If feasible, an anastomosis between the duodenal stump and colon can be made in cases in which after near total enterectomy the colon is still well vascularized. 2 However in severe cases with more extensive or even near total enterectomy, the duodenal stump may be too short for external stoma creation of too poor condition to restore bowel continuity or there may be too little bowel available to restore continuity at all. In these cases, prevention of blow out of the stump is crucial.…”
Section: Introductionmentioning
confidence: 99%